A Role for Electrotonic Coupling Between Cortical Pyramidal Cells - Crodelle, Jennifer; Zhou, Douglas; Kovačič, Gregor; Cai, David (Frontiers in Computational Neuroscience, 2019)
Many brain regions communicate information through synchronized network activity. Electrical coupling among the dendrites of interneurons in the cortex has been implicated in forming and sustaining such activity in the cortex. Evidence for the existence of electrical coupling among cortical pyramidal cells, however, has been largely absent. A recent experimental study measured properties of electrical connections between pyramidal cells in the cortex, deemed "electrotonic couplings." These junctions were seen to occur pair-wise, sparsely, and often coexist with electrically-coupled interneurons. Here, we construct a network model to investigate possible roles for these rare, electrotonically-coupled pyramidal-cell pairs. Through simulations, we show that electrical coupling among pyramidal-cell pairs significantly enhances coincidence-detection capabilities and increases network spike-timing precision. Further, a network containing multiple pairs possesses a rich coding structure, exhibiting large variability in its firing pattern.